A new method for preparing soft magnetic composite material from double-coated pure iron powder

CN117444194BActive Publication Date: 2026-10-09NANJING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311429856.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2026-10-09
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

目前的研究工作中,复合磁性粉末制备软磁复合材料已有一定研究基础,但仍存在饱和磁化强度较低和磁导率较低的问题

Benefits of technology

[0018] (1) The preparation method described in this invention makes better use of the differences in particle size and shape between irregular pure iron powder and spherical amorphous powder to achieve double-layer coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117444194B_ABST
    Figure CN117444194B_ABST
Patent Text Reader

Abstract

The application discloses a new method for preparing soft magnetic composite material by double-coating pure iron powder, and belongs to the technical field of soft magnetic composite material. The method comprises the following steps: pre-treating FeSiB amorphous powder; mixing the pure iron powder and the pre-treated FeSiB amorphous powder to obtain magnetic powder; using cold pressing forming to prepare a ring-shaped sample from the magnetic powder; and performing annealing heat treatment on the ring-shaped sample. The FeSiB amorphous powder is passivated by phosphoric acid, and then the pure iron powder is coated by using the particle size difference and shape difference between the amorphous powder and the pure iron powder, so that the double-composite coating is realized. The sample obtained by the method has the advantages of large density, small magnetic loss, high effective permeability, simple pressing process, small pressing pressure and application under high-temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of soft magnetic composite material technology, and in particular, it is a new method for preparing soft magnetic composite materials by double coating of pure iron powder. Background Technology

[0002] Soft magnetic composite materials are made by pressing ferromagnetic powder coated with an insulating layer. They have higher resistivity and lower eddy current losses than traditional metallic soft magnetic materials, and possess higher saturation magnetic induction than ferrites. They are widely used in electronic communications, radar, power switches, and other fields. Amorphous materials, due to the absence of magnetocrystalline anisotropy, high saturation magnetic induction, good frequency stability, and excellent DC bias characteristics, have become an important branch of soft magnetic composite materials. Among them, FeSiB, with its high resistivity, high saturation magnetic induction, and low coercivity, is the most representative amorphous soft magnetic material.

[0003] The preparation process of soft magnetic composite materials includes powder preparation, insulating coating, compression molding, and stress-relief annealing. Among these, the insulating coating and annealing processes play a crucial role in the performance of amorphous soft magnetic composite materials. Insulating coating helps increase interparticle resistance, reduce eddy current losses, and improve the high-frequency performance of the composite material. Stress-relief annealing can eliminate the internal stress generated by the deformation of magnetic powder during compression, reducing hysteresis losses. To further improve the magnetic properties of SMCs, recent studies have focused on using composite powders such as Fe / amorphous Fe powder, carbonyl Fe / FeSiB amorphous, carbonyl Fe / FeSiBCCr amorphous, and carbonyl Fe / FeSiB amorphous as magnetic matrices to further enhance the magnetic properties of SMCs. In addition, the insulating coating on the powder surface is very important for effectively reducing the iron loss of SMCs and thus improving their frequency characteristics. The choice of inorganic coatings is usually based on their thermal stability, and they are mainly divided into three categories: acids, metal oxides, and ferrites. Typically, acids react directly with magnetic powder to form an insulating coating on its surface, such as phosphoric acid and nitric acid. Acidic coating processes are easy to implement, especially phosphating, which is a mature method. A thin insulating layer results in minimal magnetic dilution, and phosphated SMCs offer low iron loss and cost advantages. Current research has a certain foundation in preparing soft magnetic composites using composite magnetic powders, but issues such as low saturation magnetization and low permeability remain. However, with a single magnetic matrix, studies have shown that low magnetic loss and high soft magnetic properties can be simultaneously achieved by using soft magnetic materials as coating layers or through multilayer coating. Summary of the Invention

[0004] The purpose of this invention is to address the problems existing in the prior art by providing a method for preparing soft magnetic composite materials using phosphoric acid-passivated FeSiB amorphous magnetic powder double-coated with pure iron powder. This invention utilizes phosphoric acid-passivated high-resistivity FeSiB amorphous magnetic powder as a coating layer to achieve double coating of pure iron powder, thereby obtaining high saturation magnetization and effective permeability while maintaining low magnetic loss.

[0005] The technical solution to achieve the objective of this invention is: a new method for preparing soft magnetic composite materials by double-coating pure iron powder, the method comprising the following steps:

[0006] Step 1: Pretreatment of FeSiB amorphous powder;

[0007] Step 2: Mix pure iron powder and pretreated amorphous FeSiB powder to obtain magnetic powder;

[0008] Step 3: Use cold pressing to form a ring-shaped sample from the magnetic powder;

[0009] Step 4: Perform annealing heat treatment on the ring-shaped sample.

[0010] Furthermore, in step 1, the FeSiB amorphous powder specifically refers to FeSiB powder prepared using a water-gas atomization method. 93.6 Si 3.2 B 3.2 Amorphous powder particles, the powder is spherical, and its median particle size is 20.3 μm.

[0011] Further, the pretreatment in step 1 includes: diluting a 0.2 wt.% phosphoric acid solution with a 10 wt.% acetone solution, adding FeSiB amorphous powder and stirring evenly, then baking to allow the acetone to fully evaporate, to obtain dry phosphoric acid passivated FeSiB amorphous powder particles.

[0012] Furthermore, the pure iron powder used in step 2 is the main raw material. The pure iron powder is obtained by water atomization, has an irregular shape, and a median particle size of 103 μm.

[0013] Further, the specific implementation of powder mixing in step 2 is as follows: using phosphoric acid passivated FeSiB amorphous powder as a coating material, adding phosphoric acid passivated FeSiB amorphous powder in different mass ratios to pure iron powder in sequence, and then adding 0.5 wt.% zinc stearate as a lubricant. After that, the powder is mixed in a planetary powder mixer for 30 minutes; the mass ratios of the phosphoric acid passivated FeSiB amorphous powder in different mass ratios are 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, and 30 wt.%, respectively.

[0014] Furthermore, the pressing pressure required in step 3 is 650 MPa.

[0015] Furthermore, the outer diameter of the annular sample obtained in step 3 is 18.4 mm and the inner diameter is 12 mm.

[0016] Furthermore, the conditions required for the annealing heat treatment in step 4 are: heat treatment at 400°C under argon protection for one hour.

[0017] Compared with the prior art, the significant advantages of this invention are:

[0018] (1) The preparation method described in this invention makes better use of the differences in particle size and shape between irregular pure iron powder and spherical amorphous powder to achieve double-layer coating.

[0019] (2) The preparation method described in this invention can improve the stable frequency range of effective permeability and has high effective permeability, which can correspondingly broaden the frequency of use of the material.

[0020] (3) The preparation method described in this invention can effectively achieve double-layer coating of magnetic powder, using less non-magnetic coating layer, and can obtain higher saturation magnetization, lower coercivity, and lower magnetic loss. With the increase of the proportion of phosphoric acid passivated FeSiB amorphous particles added, the effective permeability of the soft magnetic composite material is high, and the eddy current loss is effectively reduced. When 25 wt.% of phosphoric acid FeSiB amorphous powder is added, the effective permeability of the sample is 82, the saturation magnetization is 186.8 emu / g, and the magnetic loss is 55.7 kW / m3 under 100 kHz, 10 mT test.

[0021] (4) The preparation method described in this invention requires a low pressing pressure, only 650 MPa, but the resulting sample has a high density.

[0022] (5) The sample prepared by the preparation method described in this invention does not contain organic coating and can be adapted to the application environment at high temperature.

[0023] The present invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description

[0024] Figure 1 This is a flowchart of a novel method for preparing soft magnetic composite materials using double-coated pure iron powder, as per the present invention.

[0025] Figure 2 This is a scanning electron microscope image of the pure iron powder used in this invention.

[0026] Figure 3 This is a scanning electron microscope image of the phosphoric acid passivated FeSiB amorphous powder used in this invention.

[0027] Figure 4 This is a graph showing the density variation of the sample prepared according to the present invention as a function of the proportion of added phosphoric acid passivated FeSiB amorphous powder.

[0028] Figure 5 The cross-sectional microstructure of the sample obtained in this invention is shown. The sample contains 25 wt.% of phosphoric acid passivated FeSiB amorphous powder.

[0029] Figure 6 This is a schematic diagram showing the effective magnetic permeability of samples prepared according to the present invention with different pure iron powder / phosphoric acid passivated FeSiB amorphous powder content ratios in the frequency range of 1kHz to 100kHz.

[0030] Figure 7 This is a schematic diagram showing the magnetic loss of samples prepared according to the present invention with different pure iron powder / phosphoric acid passivated FeSiB amorphous powder contents in the frequency range of 1kHz to 100kHz. The test was conducted at B... m =10mT was performed. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0032] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. If the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0033] On the one hand, combined with Figure 1 This invention provides a novel method for preparing soft magnetic composite materials by double-coating pure iron powder, the method comprising the following steps:

[0034] Step 1: Pre-treat the FeSiB amorphous spherical powder, including diluting 0.2wt.% phosphoric acid solution with 10wt.% acetone solution, then adding FeSiB amorphous powder particles and stirring evenly for passivation, followed by baking to allow the acetone to fully evaporate, to obtain dry phosphoric acid passivated FeSiB amorphous powder particles.

[0035] Step 2: Mix irregular pure iron powder and pretreated FeSiB amorphous spherical powder. Specifically, the following steps are taken: use phosphoric acid passivated FeSiB amorphous powder as a coating material, add phosphoric acid passivated FeSiB amorphous powder in different mass ratios to pure iron powder in sequence, add zinc stearate as a lubricant, and then mix the powder in a planetary mixer for 30 minutes.

[0036] Step 3: The magnetic powder is formed into a ring sample by cold pressing; the pressing pressure is 650 MPa, and a ring sample with an outer diameter of 18.4 mm and an inner diameter of 12 mm is obtained.

[0037] Step 4: Heat treat the sample; the required conditions are argon protection heat treatment at 400℃ for one hour followed by annealing to eliminate the internal stress caused by pressing.

[0038] Here, the metal matrix of the soft magnetic composite material of the present invention uses pure iron powder and FeSiB amorphous powder. Pure iron powder as the matrix meets the performance requirements of strip material having certain strength, high plasticity, low hardness and good soft magnetic performance. FeSiB amorphous powder has higher resistivity, higher permeability and lower coercivity, which ensures the overall structural strength and soft magnetic properties of the soft magnetic composite material.

[0039] Preferably, the FeSiB amorphous powder in step 1 is FeSiB powder prepared by water-air atomization. 93 .6Si 3.2 B 3.2 Amorphous powder particles, the powder is spherical, and its median particle size is 20.3 μm.

[0040] Preferably, the pure iron powder is the main raw material, which is obtained by water atomization, has an irregular shape, and a median particle size of 103 μm.

[0041] Preferably, the phosphoric acid coating concentration is 0.2 wt.%.

[0042] Preferably, the mass ratios of the phosphoric acid passivated FeSiB amorphous powders are 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, and 30 wt.%, respectively.

[0043] Preferably, during the powder mixing process, the zinc stearate content is 0.5 wt.% zinc stearate.

[0044] On the other hand, a system for preparing soft magnetic composite materials by double-coating pure iron powder is provided, the system comprising:

[0045] The first module is used for pretreatment of FeSiB amorphous powder;

[0046] The second module is used to mix pure iron powder and pretreated amorphous FeSiB powder to obtain magnetic powder.

[0047] The third module is used to form ring-shaped samples from magnetic powder using cold pressing.

[0048] The fourth module is used for annealing heat treatment of ring-shaped samples.

[0049] Specific limitations regarding the system for preparing soft magnetic composite materials using double-coated pure iron powder can be found in the above description of the new method for preparing soft magnetic composite materials using double-coated pure iron powder, and will not be repeated here. Each module in the aforementioned system for preparing soft magnetic composite materials using double-coated pure iron powder can be implemented entirely or partially through software, hardware, or a combination thereof. These modules can be embedded in or independent of the processor in a computer device, or stored in the memory of a computer device as software, so that the processor can call and execute the corresponding operations of each module.

[0050] The preparation and performance testing of the soft magnetic composite material of the present invention will be further verified and explained below through Examples 1 to 5.

[0051] Example 1

[0052] (1) The pure iron powder used in Example 1 has a purity of 99.9%, is produced by water atomization, has an irregular shape, a median particle size of 103 μm, and a mass ratio of 90% pure iron powder.

[0053] (2) The FeSiB amorphous powder used in Example 1 is composed of Fe 93.6 Si 3.2 B 3.2 The amorphous FeSiB powder was prepared by water vapor atomization and was spherical. 0.2 wt.% phosphoric acid solution was diluted with 10 wt.% acetone solution, and the amorphous FeSiB powder was dispersed in the solution for passivation. After stirring for 80 minutes, the powder was dried to obtain phosphoric acid passivated amorphous powder. The median particle size of the passivated amorphous powder was 20.3 μm, and the mass percentage of the phosphoric acid passivated amorphous powder was 10%.

[0054] (3) Add zinc stearate to the powders in (1) and (2) above, and mix with a planetary stirrer for 30 minutes until homogeneous.

[0055] (4) The mixed powder obtained in (3) was cold-pressed into a ring-shaped sample with a forming pressure of 650 MPa. The inner diameter of the ring-shaped sample was 12 mm and the outer diameter was 18.4 mm.

[0056] (5) Place the ring-shaped sample obtained in (4) in a vacuum furnace and anneal it at 400°C for one hour under argon protection.

[0057] (6) The annealed sample obtained in (5) was insulated and wrapped with primary and secondary coils. The magnetic loss was tested using an AC / DC BH analyzer MATS-2010S. The test conditions were B. m =10mT, with a test range of 1kHz to 100kHz.

[0058] (7) The sample slices prepared in (5) were tested for saturation magnetization using the DynaCool-9 PPMS testing platform with a maximum applied magnetic field of 10000 Oe.

[0059] (8) The sample prepared in (5) is insulated and wrapped with a coil. The inductance value is then tested using an inductance-capacitance-resistance meter (Hioki IM3532) from 1 kHz to 100 kHz. The effective permeability is calculated from the inductance value.

[0060] Examples 2-5

[0061] (1) In Examples 2-5, the mass percentage of pure iron powder decreased by 5% in each example, changing from 85% to 70%.

[0062] (2) In Examples 2-5, the mass percentage of phosphoric acid passivated FeSiB amorphous powder increased by 5% in each example, changing from 15% to 30%.

[0063] (3) Same as (3) in Example 1.

[0064] (4) is the same as (4) in Example 1.

[0065] (5) is the same as (5) in Example 1.

[0066] (6) is the same as (6) in Example 1.

[0067] (7) is the same as (7) in Example 1.

[0068] (8) is the same as (8) in Example 1.

[0069] The density ρ and effective permeability μ obtained in the above embodiments e The values ​​for (100kHz) and magnetic loss Pcv (10mT / 100kHz) are shown in Table 1 below.

[0070] Table 1. Mass ratios, density ρ, and effective permeability μ of Examples 1-5 e (100kHz) and magnetic loss Pcv(10mT / 100kHz)

[0071]

[0072] As shown in the table above, the sample obtained by the method of this invention has high density, low magnetic loss, and high effective permeability. Furthermore, the required pressing process is simple, the pressing pressure is low, and it can be applied under high-temperature conditions. Furthermore, Table 1 shows that when the mass percentage of pure iron powder / phosphoric acid passivated FeSiB amorphous powder is 75 / 25, a soft magnetic composite material with high effective permeability and low magnetic loss can be prepared, exhibiting excellent comprehensive soft magnetic properties. The method of this invention, at room temperature, enables rapid and controllable production of Fe-based soft magnetic composite materials, and is environmentally friendly and energy-efficient.

[0073] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention without departing from its spirit and scope should be included within the protection scope of the present invention.

Claims

1. A method for preparing soft magnetic composite materials by double-coating pure iron powder, characterized in that, The method includes the following steps: Step 1: Pretreatment of FeSiB amorphous powder; Step 2: Mix pure iron powder and pretreated FeSiB amorphous powder to obtain magnetic powder; Step 3: Use cold pressing to form a ring-shaped sample from the magnetic powder; Step 4: Perform annealing heat treatment on the ring-shaped sample; In step 1, the FeSiB amorphous powder specifically refers to FeSiB powder prepared by water-gas atomization. 93.6 Si 3.2 B 3.2 Amorphous powder particles, the powder is spherical, and its median particle size is 20.3 μm; The pretreatment described in step 1 includes: diluting a 0.2 wt.% phosphoric acid solution with a 10 wt.% acetone solution, adding FeSiB amorphous powder and stirring evenly, then baking to allow the acetone to fully evaporate, to obtain dry phosphoric acid passivated FeSiB amorphous powder particles. The pure iron powder mentioned in step 2 is obtained by water atomization, and has an irregular shape with a median particle size of 103 μm; Step 2, specifically the powder mixing process, involves using phosphoric acid-passivated FeSiB amorphous powder as a coating material. This powder is added to pure iron powder, followed by the addition of 0.5 wt.% zinc stearate as a lubricant. The powder is then mixed for 30 minutes using a planetary powder mixer. The mass ratio of the phosphoric acid-passivated FeSiB amorphous powder is 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, or 30 wt.%, where wt.% represents the mass ratio of FeSiB amorphous powder to the soft magnetic composite material. The conditions required for the annealing heat treatment in step 4 are: heat treatment at 400℃ under argon protection for one hour.

2. The method for preparing soft magnetic composite materials by double-coating pure iron powder according to claim 1, characterized in that, The pressing pressure required in step 3 is 650 MPa.

3. The method for preparing soft magnetic composite materials by double-coating pure iron powder according to claim 1, characterized in that, The outer diameter of the annular sample obtained in step 3 is 18.4 mm and the inner diameter is 12 mm.

4. A system for preparing soft magnetic composite materials from double-coated pure iron powder based on the method described in any one of claims 1 to 3, characterized in that, The system includes: The first module is used for pretreatment of FeSiB amorphous powder; The second module is used to mix pure iron powder and pretreated FeSiB amorphous powder to obtain magnetic powder. The third module is used to form ring-shaped samples from magnetic powder using cold pressing. The fourth module is used for annealing heat treatment of ring-shaped samples.

Citation Information

Patent Citations

  • Fe / FeSiB composite magnetic powder core and preparation method thereof

    CN107958762A

  • Double-main-phase soft magnetic composite material and preparation method thereof

    CN113555178A